FACTORS CONTRIBUTING TO THE ACCEPTANCE OF VERIFY HALAL APP AMONG THE MALAYSIAN MUSLIM CONSUMERS (International Journal of Islamic Business, 2024)
The presence of a halal mark on a food product serves as an indicator that the food has been certified as halal and is deemed suitable for consumption according to Islamic dietary guidelines and safety standards. However, the increased demand for halal food in the market has led many business owners to exploit this trend by intentionally misleading consumers with false claims of halal certification. To address these issues, the Verify Halal app platform was developed. However, there is a lack of research on the factorscontributing to its acceptance. As such, this study explores the factors contributing to the acceptance of Verify Halal app among the Malaysian Muslim consumers. To achieve this objective, survey questionnaires were distributed online and face-to-face to collect data from 250 Muslim respondents in the Klang Valley area of Malaysia. The data collected were analyzed using SPSS. The results indicate that religiosity, perceived ease of use, perceived usefulness, and social influence contribute positively and significantly to the acceptance of the Verify Halal app. However, trust contributes negatively and insignificantly to its acceptance among Malaysian Muslim consumers. The findings of this study have serious implications for several entities, including halal business owners, halal consumers, halal app developers, and government entities. Specifically, halal business owners should ensure that information about their products listed on the app is accurate, current, and in compliance with halal standards. The findings call on halal consumersto frequently use the app to search for and purchase halal-certified products, which could contribute to the development of an effective community for other users. Halal app developers should prioritize user-centric design principles, which will not only increase initial engagement but also generate positive reviews and referrals, thereby contributing to the Verify Halal app’s market reputation. Finally, various forms of government incentives, such as grants and collaborations, can be provided to facilitate the advancement ofthe Verify Halal app.